Language as Means of Communication - Anna Hlavnova (Communications - Scientific letters of the University of Zilina, 1999)
The paper deals with the question of languages as means of communication. It analyses language instruction in institutions of higher learning. Areas of special interest are mentioned and some ways leading to the integration of all language skills into instruction are suggested.